WORK-LIFE BALANCE AND CAREER SUCCESS OF ACADEMIC STAFF IN NIGERIAN PUBLIC UNIVERSITIES: THE MODERATING ROLE OF DIGITAL TECHNOLOGY - Don-Solomon, Amakiri (INTI International University, 2023)
Achieving success in career is a major accomplishment an average employee looks forward to and the academics of Nigerian Public Universities are not an exception. The purpose of this research was to examine the empirical relationship between work-life balance and career success of academic staff of Nigerian Public Universities with digital technology as the moderating variable. Work-life balance dimensions used are flexi-time and job-sharing, while, job security, and promotion were used to measure career success. 6,836 academic staff formed the population of the study. Taro Yamane's formula was used to obtain a sample size of 378. Descriptive survey design was used. Spearman Rank Order Correlation Coefficient and Partial Correlation Coefficient was used as tool for analysis. Findings showed that flexi-time and job sharing have low but positive significant relationship with job security and promotion.Digital technology positively and significantly influences the relationship between work-life balance and career success. Based on the findings the study recommends policymakers at every level involved in university management to advocate for academic’s flex-time arrangement, this will increase their satisfaction on the job thereby jettison the intention to quit. also, public universities should employ more academic staff for effective job-sharing practice.